Mapping European security after Kosovo - Ham, Peter van, 1963-; Medvedev, Sergei (Manchester University Press, 2002)
This study provides new horizons on how Kosovo has shaped the new Europe - breaking down traditional assumptions in the field of security studies by sidelining the theoretical worldview that underlies mainstream strategic thinking on recent events in Kosovo.